Biallelic mutations in CDC20 cause female infertility due to oocyte maturation abnormality - Guangzhong Jiao; Jinhao Xing; Zhaoli Du; Hongchu Bao; Xiaoyan Liu (Gynecological Endocrinology)
Oocyte maturation arrest (OMA) may occur at different stages, including the germinal vesicle (GV), metaphase I (MI), and metaphase II (MII). A total maturation arrest of human oocytes is rarely observed during in vitro fertilization (IVF). We have identified a case of infertile female for whom all oocytes fail to mature and are arrested at MI. Whole-exome sequencing revealed a compound heterozygous mutant (c.533C > A: p.Val458Ala; c.1373T > C: p.Ala178Glu) in cell division cycle 20 (CDC20). Through rigorous validation using Sanger sequencing technology, both of her parents have been confirmed as genetic carriers of these specific mutations. Based on the three-dimensional (3D) structures of the CDC20 protein used to assess the effect of the mutant, the mutant causes a change in hydrogen bond in the protein structure, which may affect the stability of the mutant protein. Previous studies have firmly established CDC20 as a pivotal member of the cell cycle regulation family, playing an indispensable role in the transition from metaphase to anaphase during cell division. Our findings not only broaden the current understanding of CDC20 gene mutations but also profoundly illuminate how these mutations serve as potential genetic mechanisms underlying the arrest of oocyte maturation.